Management of attention deficit hyperactivity disorder in children and adolescents - Toh, Chin Lee; Hashim, Aili Hanim; Bahar, Norharlina; Cheong, Sau Kuan; Sundram, Permalatha; Muhd Ramli, Eni Rahaiza; Sivasampu, Sheamini; Mohammed, Fauziah; Saad, Supiah (CPG Secretariat, Ministry of Health Malaysia, 2008)
This guideline is meant to be a guide for clinical practice, based on the best available evidence at the time of development. Adherence to this guideline may not necessarily guarantee the best outcome in every case. Every health care provider is responsible for the management of his/her unique patient based on the clinical picture presented by the patient and the management options available locally.